With algebraic fractions using different denomonators say x + 6 - 3 = 0 x x -4 Could somebody please advise the correct method used to make both the denominators the same? Thanks David
Follow Math Help Forum on Facebook and Google+
Originally Posted by David Green With algebraic fractions using different denomonators say x + 6 - 3 = 0 x x -4 $\displaystyle \frac{x+6}{x} - \frac{3}{x-4} = 0$ $\displaystyle \frac{(x-4)(x+6)}{x(x-4)} - \frac{3x}{x(x-4)} = 0$ do yourself a favor and learn how to format equations and expressions using Latex ...
Originally Posted by skeeter $\displaystyle \frac{x+6}{x} - \frac{3}{x-4} = 0$ $\displaystyle \frac{(x-4)(x+6)}{x(x-4)} - \frac{3x}{x(x-4)} = 0$ do yourself a favor and learn how to format equations and expressions using Latex ... Thanks for that
View Tag Cloud